THE ROLE OF ENGLISH CLUB FOR STUDENTS’ ENGLISH SKILLS AT SMA RAUDLATUL ULUM GONDANGLEGI - MOCHAMAD HAFID RONI; MULIS (IAI Al-Qolam, 2023)
The aim of this research is to analyze the role of the English club in influencing students' English skills at SMA Raudlatul Ulum Gondanglegi. The method used in this research is a qualitative research method. The data were obtained by interviews to some students. Qualitative research is based on primary data and secondary data. Primary data was obtained through interviews while secondary data was obtained through journals and books related to research. Interview was done by researcher to obtain information from students regarding the role of English club at school. Then, the researcher analyzed the data. The participants of this research were students taking part in an English club. The researcher involved five students to be informant. Based on the data collected by the researcher, it shows that the English club is considered to have a very important role in supporting students' English language skills. The students said that the English club had a unique way of teaching English in class. They mentioned that English club activities played an important role in the development of their English skills. They also said that they were happier and more comfortable learning English in an English club than studying in class as usual. Students who join the English club understand English better than students who do not join the English club.